2017
DOI: 10.1186/s13098-016-0200-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic protocol for gestational diabetes mellitus (GDM) (IADPSG/ADA, 2011): influence on the occurrence of GDM and mild gestational hyperglycemia (MGH) and on the perinatal outcomes

Abstract: BackgroundIn August 2011, the Specialized Center for Diabetes and Pregnancy of the Botucatu Medical School/Unesp adopted a new diagnostic protocol for gestational diabetes mellitus, recommended by the American Diabetes Association and the International Association of the Diabetes and Pregnancy Study Group. The glycemic profile was evaluated using the 75-g oral glucose tolerance test (OGTT) used to diagnose mild gestational hyperglycemia, recognized and treated in our department as gestational diabetes mellitus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…According to the literature, all these possibilities could mask the expected differences in perinatal outcomes. In IADPSG protocol studies, the small sample size was used to explain the increasing incidence of GDM (10 to 25%) and limited effect on perinatal results [35][36][37][38]. Overweight or obesity alone has been associated with the risk of developing GDM and Metabolic Syndrome (MetS).…”
Section: Plos Onementioning
confidence: 99%
“…According to the literature, all these possibilities could mask the expected differences in perinatal outcomes. In IADPSG protocol studies, the small sample size was used to explain the increasing incidence of GDM (10 to 25%) and limited effect on perinatal results [35][36][37][38]. Overweight or obesity alone has been associated with the risk of developing GDM and Metabolic Syndrome (MetS).…”
Section: Plos Onementioning
confidence: 99%
“…Accumulated studies have shown that pregnancy complications, such as pregnancy-induced hypertension (PIH), gestational diabetes mellitus (GDM) and intrahepatic cholestasis (ICP), could affect perinatal situations [7][8][9][10][11][12][13]. Glucose plays important roles in brain metabolism and brain development in newborns.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we evaluated the value of risk factor for predicting not only GDM (using 75-g OGTT 3 as gold standard), but also MGH (using glucose profile as gold-standard). Although this approach makes comparison with other studies difficult, it is justified by the fact that the new GDM diagnostic criteria are not met by 17% of our patients, who otherwise would be left untreated to suffer maternal and perinatal consequences [4][5][6] .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we combine glucose profile testing (GP) with a 75g-OGTT to identify women with mild gestational hyperglycemia (MGH), who represent 17.3% of our patient population and do not meet GDM diagnostic criteria 4 . Women with MGH show the same maternal and fetal outcomes seen in those with GDM and, therefore, should be identified and treated for glycemic control during pregnancy 5,6 .…”
Section: Introductionmentioning
confidence: 99%